Development and analysis of a mathematical model of combustion оf coal-water fuel particles (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article discusses coal-water fuel, which is one of the ways to increase the efficiency of coal use. The combustion process of a coal-water fuel particle was divided into appropriate stages. The solution to the problem of the 1st stage of the combustion process - “Heating until water evaporates” is automated using the finite difference method in the Python programming language. The results obtained by the numerical method were compared with the experimental ones and analyzed.
Keywords: coal-water fuel, combustion of a coal-water fuel particle, mathematical model of combustion of a coal-water fuel particle, Python programming language, finite difference method.